A Program to Improve Arabic Writing Skill with Media Quizizz at Mutiara Anak Sholeh Elementary School - Anisa Nasrul Rusandi; Muhammad Thohir (Journal of Arabic Language Studies and Teaching, 2022)
This study demonstrates that only E-Learning media, such as Quizizz Media, are necessary to improve students' ability to comprehend the material. Quizizz Media is a mixed learning media that is varied and exciting for children. It is effectively used as an Arabic writing skill learning medium that improves students' skills. Quizizz Media, as one of the media used in the classroom, also received a positive response from youngsters. This research aims to determine the production, use, and effectiveness of Arabic learning media based on quizizz in improving the Arabic language writing skills at Sd Mutiara Anak Sholeh. Observation, information, and interviews were used to acquire descriptive qualitative research data and information. The study's findings suggest that Quizizz Media is an engaging, effective, and highly motivating media for children to use in and out of the classroom.